RANDOMIZED COMPARATIVE INTERVENTION STUDY OF HELICAL BLADE AND SCREW PROXIMAL FEMUR NAIL IN THE TREATMENT OF INTERTROCHANTERIC FEMUR FRACTURES. - Meena, Dr. Umesh Kumar; Jangir, Dr. Lokesh Kumar; Meena, Dr. Ram Prasad; Vashistha, Dr. Shailendra (Student's Journal of Health Research Africa, 2023)
Introduction: In the trochanteric region of the femur fractures are comparatively serious and their treatments can be done after hospitalization of the patient. The surgical procedure to fix the fractures helps in achieving mobilization of the bone. Intramedullary devices such as PFN and DHS are used for fixation. Objective: To compare the efficacy of Helical Blade PFN and Screw PFN for treating fractures in the intertrochanteric region. Methods: This study was randomized comparative research conducted among adults and elderly patients (Aged>50 years) during the study period from June 2018 to December 2020, where the patients were divided into two arms/groups where Group I patients (n=25) were treated with Helical PFN (PFNA2); Group II patients (n=25) were treated with Screw PFN and followed up prospectively. Results: Most of the patients in the present study were from the age group of more than 60 years. X-ray exposure shots during surgery were with mean of 36.08 in 25 patients of group I. The increase in X-ray exposure was due to the requirement of putting two screws in PFN rather than a single helical screw in PFNA2. Group I showed lower Singh's index with better results when compared with that of group II. Shortening of the limb by 3 cm ( which is maximum shortening) was not found in any patient group I, whereas, in group II, 1 patient showed a maximum shortening of 3 cm. Conclusion: Based on this study’s results, we can conclude that PFNA2 (Helical Blade PFN) is better than Screw PFN in the treatment of Intertrochanteric Femur Fractures. PFNA2 has a better contact area, lesser complications than Screw PFN in addition to lesser surgical duration and blood loss. Recommendation: Prosthetic replacement is recommended for unstable intertrochanteric fractures because of the complications that may occur after internal fixation.